Supply chain management : strategy, planning, and operation / Sunil Chopra. - Chopra, Sunil, 1960- (Pearson, 2019)
'Supply Chain Management' illustrates the key drivers of good supply chain management in order to help students understand what creates a competitive advantage. It also provides strong coverage of analytic skills so that students can gauge the effectiveness of the techniques described.